Determination of the germination temperature of Moringa oleifera seeds with support of vigor tests - Navarro, Marlen; Cicero, S. M.; Gomes-Junior, F. G. (Cuban Journal of Agricultural Science, 2016)
Samples from six seeds lots of Moringa oleifera cv. Supergenius were used with the objective of determing the optimum temperature for the germination test of this species. The temperatures 25°C; 30°C and 20-30°C were evaluated. The used vigor tests were: germination test (G), germination rate index (GRI), electric conductivity test (EC) and the plantlet computerize analysis through the SVIS software and the indexes that are automatically generated. All variables were subjected to analysis of variance, differences were declared significant according to Tukey test (P≤0.05) with the help of the statistical package SPSS 22.0.The EC values showed better seed quality in the lots two and four. For G and FGC, the lot four showed the highest value for the evaluated temperatures. Although for FGC the lot four at 30°C did not differ from lots one, two and six. The best GRI performances were for the lots one, two, four, five and six at 30°C.For the indexes generated by the SVIS, the vigor index (VI) in lot four at 30°C was higher, as for the growth index (GI). The analysis of the uniformity index (UI) for temperatures showed differences for the lots two, four and five; always with the highest values for 30°C.For plantlets length (PL) lots one, five and six showed the best performance at 30°C without differ from 25°C. Neither differ lot one for25 and 30°C. While lot four showed higher performance for PL at 30°C in relation to other temperatures. In a general way, the study results showed the best performance of moringa seeds at 30°C. Key words: moringa, germination, SVIS®, vigor.